Efeitos socioeconômicos do Agroamigo : uma estratégia de fortalecimento da agricultura familiar no estado de Sergipe - Brito, Volnandy de Aragão (2017)
Agroamigo is a program of rural microcredit inserted in the Methodology of the National Program for Strengthening Family Agriculture and National Program for Oriented Productive Microcredit (PNMPO). IT IS Operated at Banco do Nordeste do Brasil in the Northeastern and Northern States of Minas Gerais and Espirito Santo through partnership with Instituto Nordeste Cidadania. Its mission is to promote rural development through the granting of small financing (quantitative vision) for investments and costing in agricultural and non-agricultural activities, whether or not rotating, as well as credit counseling and technical monitoring (qualitative vision) over the term Of the financing. As a productive and oriented rural credit, Agroamigo transcends the mere granting of bank credit and is an instrument of a local and regional development policy, which should be integrated with other regional development policies such as PAA, PGPAF, Proagro, The Family Grant, the Light for All, etc. in order to maximize its social and economic effects. The objective of this work is to explain the effects of the individual perspective and the loco-regional perspective, with Agroamigo, considering the vertiginous and ascending growth in the quantitative of contracted operations in this methodology. It investigates whether this quantitative growth has been accompanied by social and financial changes in the borrowers and their socioeconomic externalities in the municipalities, by inducing a greater flow of capital and circulation of goods and services. The regional area analyzed is the main municipalities "borrowers" in the State of Sergipe, having defined the timeline from 2005 to 2015. It begins with a conceptual and historical-factual approach on PRONAF, the emergence of Agroamigo and Their inclusion in the PNMPO methodology. It proceeds with the presentation of the data collected, the field research performed, the expected results. Finally, it discusses the data and information in light of the thesis raised of the effects of Agroamigo in the regional development. The analysis of the data ratified the positive impacts of Agroamigo on income generation and its effects on the local economy, which justifies the choice of the theme as a relevant issue within the framework of regional development policy and in the process of organizing the rural area.